2021
DOI: 10.1177/15570851211034560
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Consent and Communication Among the Sexual Minoritized: The Role of Heteronormative Sex Education, Trauma, and Dual Identities

Abstract: Prior research and the #MeToo movement have recognized the complexities of sexual consent and how it contributes to experiences of sexual violence. A heteronormative perspective often dominates discussions on sexual violence at the expense of lesbian, gay, bisexual, transgender, queer, and other sexual minoritized individuals’ (LGBTQ+) experiences. Utilizing focus groups with LGBTQ+ people to discuss sexual consent, themes relating to sex education, defining sex in queer relationships, trauma and victimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 61 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…Most notably, more than half of the scripts of TGD students included an open communication theme. This finding parallels prior research, which has found that open communication is common among LGBTQ+ individuals’ sexual scripts and is much more prevalent in LGBTQ+ individuals’ scripts than in heterosexual individuals’ scripts (de Heer et al, 2021; Gabb, 2022). This likely reflects, at least in part, the perceived importance of communication in ensuring safety and in preventing potentially triggering experiences during sex for TGD college students.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Most notably, more than half of the scripts of TGD students included an open communication theme. This finding parallels prior research, which has found that open communication is common among LGBTQ+ individuals’ sexual scripts and is much more prevalent in LGBTQ+ individuals’ scripts than in heterosexual individuals’ scripts (de Heer et al, 2021; Gabb, 2022). This likely reflects, at least in part, the perceived importance of communication in ensuring safety and in preventing potentially triggering experiences during sex for TGD college students.…”
Section: Discussionsupporting
confidence: 88%
“…However, informed by the sexual scripts of LGBQ+ individuals, it seems likely that TGD college students’ scripts will diverge from the cisgender and heterosexual narratives woven into the overarching culture, given that these scripts do not likely encapsulate the experiences of TGD college students. Again, research among LGBQ+ individuals and couples demonstrates this, as their scripts often reflect engaging in more open communication about sexual preferences, desires, and boundaries, whereas these discussions are much less common within heterosexual individuals’ and couples’ scripts (de Heer et al, 2021; Gabb, 2022). This also appears true for LGBQ+ college students, as there is quantitative evidence that LGBQ+ college students adhere less to gendered sexual scripts than heterosexual college students (Fournier et al, 2022).…”
Section: Sexual Scripts Of Tgd College Students and Gender Minority S...mentioning
confidence: 99%
“…Moreover, shifting to a trauma-informed, anti-oppressive framework for consent education that does not rely on a binary concept opens up the possibilities for addressing persistent systemic forms of oppression that create grey areas for all youth. Notably, future research should examine the lessons for consent education from BIPOC, Two-Spirit, queer, trans and/or non-binary communities who cite a legacy of challenging binaries and refusing a normative model of consent (see Bauer 2021;Beres 2021;de Heer et al 2021). Principles of disability justice should also be incorporated into anti-oppressive, trauma-informed consent education (Wright 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research may be especially useful in deciphering factors that facilitate sexual aggression among heterosexual girls, as well as among sexual minority boys and sexual minority girls. In qualitative research, many sexual minority young adults noted that the lack of a clear sexual script (i.e., the man initiates, the woman is the gatekeeper) in same‐gender interactions both requires more discourse about consent and leaves space for miscommunication (de Heer et al, 2021; Jozkowski et al, 2014). It is also important to note that the current study did not assess whether endorsement of these risk factors was associated with the perpetration of sexual aggression in the study.…”
Section: Discussionmentioning
confidence: 99%